DISPLASIA PERKEMBANGAN PANGGUL AWAL (LAHIR HINGGA USIA 4 BULAN) - Sumarna, Vivi; Angliadi, Engeline (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Developmental dysplasia of the hip refers to a continuum of abnormalities of the immature hip that can range from subtle dysplasia to dislocation. The identification of risk factors, including breech presentation and family history, should heighten a physicianâ€™s suspicion of this condition. The diagnosis is based on physical examination. Palpable hip instability, unequal leg lengths, and asymmetric thigh skinfolds may be present in newborns with a hip dislocation, whereas gait abnormalities and limited hip abduction are more common in older children. The role of ultrasonography is controversial, but it is generally used to confirm the diagnosis and to assess hip development once the treatment is initiated. Bracing is the first-line treatment in children aged less than six months. Surgery is an option for children with unsuccessful non-operative treatment and in children who are diagnosed after six months of age. It is important to confirm the diagnosis of the developmental dysplasia of the hip in the early stage to improve the result of treatment and to decrease the risks of complications. Keywords: hip, developmental dysplasia, immature, instability, bracingÂ Â Abstrak: Displasia perkembangan panggul mengacu pada serangkaian abnormalitas pada panggul imatur yang mencakup displasia ringan hingga dislokasi. Identifikasi faktor-faktor risiko yang meliputi letak sungsang dan riwayat keluarga, harus menigkatkan kecurigaan dokter akan displasia perkembangan panggul. Diagnosis ditegakkan melalui pemeriksaan fisik. Instabilitas panggul yang dapat dipalpasi, panjang tungkai yang tidak sama, dan lipatan kulit paha yang asimetris dapat ditemukan pada bayi baru lahir dengan dislokasi panggul, sedangkan abnormalitas gait dan keterbatasan abduksi panggul lebih umum pada anak-anak yang lebih tua. Peran ultrasonografi masih kontroversial tetapi secara umum untuk mengonfirmasi diagnosis dan menilai perkembangan panggul sejak dimulainya perawatan. Penggunaan brace merupakan perawatan lini pertama pada anak-anak berusia kurang dari enam bulan. Pembedahan merupakan pilihan bagi anak-anak dengan perawatan nonoperatif yang gagal dan pada anak-anak yang didiagnosis setelah berusia enam bulan. Displasia perkembangan panggul sangat penting ditegakkan sejak dini untuk meningkatkan hasil perawatan dan mengurangi risiko komplikasi. Kata kunci: panggul, displasia perkembangan, imatur, instabilitas, brace